EMPOWERMENT OF COMMUNITIES THROUGH PKBM LEMBAGA SENI BELAJAR DI DESA SIABU KECAMATAN BANGKINANG KABUPATEN KAMPAR - Wahyuni, Sri Wahyuni Sri; Bahar, Aswandi Bahar Aswandi; Irja, Desti Irja Desti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: research it is based on the low empowerment of communities through PKBM Lembaga Seni Belajar di Desa Siabu Kecamatan Bangkinang Kabupaten Kampar. Formulation problems this research is was it the community empowerment activities through Lembaga Seni Belajar di Desa Siabu Kecamatan Bangkinang Kabupaten Kampar in good. The purpose of this research is to find community empowerment activities through Lembaga Seni Belajar di Desa Siabu Kecamatan Bangkinang Kabupaten Kampar in good. Population in this study 67 people and research sample areas 40 people with critical level 10 %, sample used is simple random sampling. An instrument data collection that is chief with 84 a statement and if the trial live 82 a statement valid for in made instrument research. Data analysis through descriptive analysis quantitative. From scratch presentation answer obtained the percentage the average (SS+S) 79,857 %. The outcome of the findings researchKata Kunci: empowerment, empowerment of communities, through PKBM